Civil Society Responses to Changing Civic Spaces - Reviewed by Vikash Kumar (Review of Development and Change)
Biekart,Kees (eds) et al. Civil Society Responses to Changing Civic Spaces. Palgrave Macmillan, 2023, 293 p. €49.99